Ways of Organizing and Developing Marketing Research in the Labor Market - Musayeva Shoira Azimovna; Umurzakova Iroda (Research Parks Publishers, 2023)
This article discusses the priority areas for the development of educational services, the current state of educational institutions that are the leading subjects of educational services in our country, and their existing problems, the content of education and its organization in the current period.